The Resistance of The Congregation of Liberal Catholic Church Saint Albanus Bandung in Preserving Existence amid Marginalization and Discrimination - Bernardus Ario Tejo Sugiarto; Abdul Syukur; Rifki Rosyad (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
The Liberal Catholic Church (LCC) has existed in Indonesia since pre-independence. It was brought by the Dutch to Indonesia along with the movements of Theosophy and Freemasonry. However, not many Indonesians know of its existence, let alone recognize it. Even many Catholics themselves do not know the intricacies of its presence in Indonesia. This is due to the common notion that Catholicism is the Roman Catholic religion that possesses the highest authority, the Pope, in Rome. If it’s compared to other Catholic sects In Indonesia, the number of adherents of the Roman Catholic religion is the largest (majority). The General Directorate of Catholic Community Guidance has always been held by Roman Catholics. The existence of LCC was never known or even acknowledged. Historically, the Roman Catholic Church has determined it to be outside the Roman Catholic Church because of its heresy. Concerning Theosophy teachings which tend to be syncretistic, not only the Roman Catholic Church is disturbed, but also religions that intend to purify their teachings. This article presents the impacts of identity politics on the existence of the LCC in Bandung and how it maintains its existence. This article is expected to open a critical understanding of the socio-political consequences of state policies on religious identity, especially for minority groups. The type of research conducted is a combination of field research and literature research. The field research method used is a qualitative method using deep conversation as a tool to collect information. The LCC has experienced marginalization and discrimination which forced them to carry out resistance to maintain their existence.